Evasiveness in Everyday Hospital Palliative Care Practice: A Focused Ethnography - Carolien van Leussen; Evelien Kuip; Renske Kruizinga; Els van Wijngaarden (Journal of Clinical Nursing, 2026)
ABSTRACT Aim To develop a practice‐based understanding of how everyday hospital routines, professional norms and organizational conditions influence the provision of palliative care for patients approaching the end of life. Design Focused ethnography informed by practice theory. Methods This study involved approximately 311 h of observation of healthcare professionals across several departments of a Dutch university hospital from January to September 2024. Data analysis followed an inductive, iterative process informed by a practice theory lens. Reporting Method This study is reported in accordance with the Standards for Reporting Qualitative Research. Results Although healthcare professionals valued palliative care and generally oriented care toward enabling patients to die in their preferred place, most often at home, palliative care was frequently characterized by evasiveness. Communication remained predominantly biomedical and focused on the present moment. Four tensions were identified: (1) Medical security versus personal intimacy; (2) system logic versus lifeworld experience; (3) information clarity versus patients' capacity to take in information and (4) medical intervention versus emotional attunement. Conclusion This study shows how evasiveness in hospital‐based palliative care is produced and sustained through biomedical routines, organizational pressures and professional and personal orientations. These factors make it difficult to realize the holistic ideals of palliative care in everyday practice. As a result, patients' fears, uncertainties and end‐of‐life wishes often remain insufficiently explored, whereas organizational routines shape what is considered appropriate and possible in clinical interactions. Impact The findings help to illuminate the complexity of everyday palliative care practices in hospital settings. Despite policy emphasis and professional commitment to palliative care, routines and organizational pressures can impede change. Efforts to improve palliative care can therefore require sustained attention to everyday practice and to the organizational and interactional conditions that constrain change. Patient or Public Contribution No patient or public contribution.